PROSES PEMBUATAN BUKU BESAR PADA PERUSAHAAN JASA DI SMK STRADA 1 - Alvita, Velinda; Hidajat, Nastasya Cindy (Jurnal Serina Abdimas, 2024)
Teaching Assistance Activities in Education Units aim to encourage students and interest in learning, talent and interest in understanding basic accounting in order to gain insight and in-depth knowledge in order to encourage the younger generation to determine the level they will take as a professional accountant and understand accounting theory. and the provisions that apply after graduating from Vocational School Strada 1. The author has been given the opportunity to teach and share knowledge with students at Vocational School Strada 1 regarding basic accounting which discusses material related to the process of making ledgers in service companies. This activity was carried out at SMK Strada 1 Gunung Sahari in 10 meetings, starting on 28 August 2023 and ending on 27 September 2023. The activity ran smoothly and was completed on time. The success of Teaching Assistance Activities in the Education Unit at Strada 1 Vocational School can be measured by an increase in scores of 28.8% during the Mid-Semester Summative Examination (STS).